Salt Lake contest party, Alaska Yukon Pacific Exposition, Seattle, July 21, 1909. - Nowell, Frank H., 1864-1950 (1909)
Two hundred and eight newspaper parties from thirty-five states as well as Canada, Alaska, the Yukon and Hawaii will visit the Alaska-Yukon-Pacific Exposition between now and Oct. 15. D.B. Duncombe, who will have charge of the entertainment of these parties, has been assured of the attendance of that number of delegations by the newspapers conducting contests, which result in the winners getting a free trip to the exposition .As a result of these contests . the exposition has received hundreds of columns of free advertising. Every day for three months many of the papers gave an entire page and in some instances two pages to announcing the contests which would result in the successful contestants getting a free trip to the ""Seattle Exposition"" as the A.Y.P. seems to be quite generally called in the East. On verso of image: Salt Lake [illeg.]Contest Party 7/21/09 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number